Medium Bandgap Polymer Donor Based on Bi(trialkylsilylthienyl‐benzo[1, 2‐b:4, 5‐b′]‐difuran) for High Performance Nonfullerene Polymer Solar Cells. Issue 20 (14th July 2017) - Bin, Haijun; Zhong, Lian; Yang, Yankang; Gao, Liang; Huang, He; Sun, Chenkai; Li, Xiaojun; Xue, Lingwei; Zhang, Zhi‐Guo; Zhang, Zhanjun; Li, Yongfang
Abstract: A new 2D‐conjugated medium bandgap donor–acceptor copolymer, J81, based on benzodifuran with trialkylsilyl thiophene side chains as donor unit and fluorobenzothiazole as acceptor, is synthesized and successfully used in nonfullerene polymer solar cells (PSCs) with low bandgap n‐type organic semiconductor (n‐OS) 3, 9‐bis(2‐methylene‐ (3‐(1, 1‐dicyanomethylene)‐indanone)‐5, 5, 11, 11‐tetrakis(4‐ hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐s‐indaceno[1, 2‐b:5, 6‐b′]‐ dithiophene (ITIC) and m ‐ITIC as acceptor.J81 possesses a lower‐lying highest occupied molecular orbital (HOMO) energy level of −5.43 eV and medium bandgap of 1.93 eV with complementary absorption in the visible–near infrared region with the n‐OS acceptor. The PSCs based onJ81 :ITIC andJ81 : m ‐ITIC yield high power conversion efficiency of 10.60% and 11.05%, respectively, with high V oc of 0.95–0.96 V benefit from the lower‐lying HOMO energy level ofJ81 donor. The work indicates thatJ81 is another promising polymer donor for the nonfullerene PSCs. Abstract : By introducing trialkylsilyl‐thienyl conjugated side chains to benzodifuran unit, a new medium bandgap polymer donor J81 is developed. The optimized nonfullerene polymer solar cells withJ81 as donor show high power conversion efficiency of 11.05%.